The impact of a passive wall combining natural ventilation and evaporative cooling on schools' thermal conditions in a hot climate. (December 2021) - Mohamed, Sara; Al-Khatri, Hanan; Calautit, John; Omer, Siddig; Riffat, Saffa
Abstract: Students' performance is negatively influenced by poor indoor environments. In Sudan that is characterised by extreme climate, providing comfortable classrooms is required to improve the educational system that suffers from restricted budgets. To address this issue, the local government in Khartoum, the capital city of Sudan, and the Ministry of Education released a joint project to construct new schools' buildings following one of two unified prototype models. This paper evaluates the impact of a new passive wall system that combines natural ventilation and evaporative cooling on the classrooms' thermal conditions. The wall consists of two brick layers that accommodate a wet porous ceramic layer, and it has two configurations. In the first configuration, the exhausted air is circulated to the system to cool it before ejecting it into the classroom. In the second configuration, the exhausted air is dissipated from the classroom through an outlet located at a wall opposite to the wall that integrates the system. The effectiveness of the system was evaluated via assessing the classrooms' conditions before and after activating it using EDSL TAS and ANSYS ICEM CFD programmes. The findings revealed considerable reductions in indoor air temperatures from 30.3–44.8 °C before activating the system to 18.9–26.5 °C and 21.3–23.8 °C after activating the system in the first and second configurations, respectively, which concludes the system effectiveness. The wall is environmentally clean as its operation barely consumes active energy, which makes it attractive considering the limited budget allocated for the education sector in Sudan. Highlights: A wall combines natural ventilation and evaporative cooling improves thermal comfort. Indoor air temperatures before activating the system were 30.3–44.8 °C. The first base case configuration reduced indoor air temperatures to 18.9–26.5 °C. The second base case configuration reduced indoor air temperatures to 21.3–23.8 °C. The wall is environmentally clean as its operation barely consumes active energy.